Leaf cuticular wax content is involved in cotton leaf curl virus disease resistance in cotton (Gossypium hirsutum L.) - Muhammad Saeed; Song Xianliang; Sun Xuezhen; Muhammad Riaz (Spanish Journal of Agricultural Research, 2019)
Cotton leaf curl virus disease (CLCuVD) limits cotton production in many cotton growing countries of the world, including Pakistan. In the past, efforts were made to combat this disease by different approaches. Cuticular wax is reported to confer resistance to plants against various biotic and abiotic stresses. Present study was designed to assess the role of cuticular wax content (WC) to resist CLCuVD infestation. The WC of 42 cotton genotypes, originating from various countries (Pakistan, USA, China, etc.), was quantified during two culture periods (2015 & 2016). Cotton germplasm was also scored for % disease index (%DI), seed cotton yield (SCY), number of bolls/plant (NB), and plant height (PHt) for the same culture periods. Significant negative correlation between WC and %DI was found during the two years of experimentation. WC was found positively correlated with SCY and NB. Six cotton genotypes (A-7233, B-557, A-162, BLANCO-3363, CIM-473, and SLH-2010-11) did not show any signs of CLCuVD infestation during both 2015 and 2016. These cotton genotypes contained relatively higher WC. The results from analysis of variance (ANOVA) demonstrated that there were significant differences among genotypes for %DI, WC, SCY, NB, and PHt. These results indicated that WC was involved in resisting CLCuVD and it also had positive effect on plant growth and yield potential. On the basis of these findings, it was concluded that cuticular wax could be used as an indirect criterion for distinguishing and selecting resistant/susceptible cotton genotypes.